Efficient and Stable TiO2:Pt–Cu(In, Ga)Se2 Composite Photoelectrodes for Visible Light Driven Hydrogen Evolution. Issue 12 (10th April 2015) - Azarpira, Anahita; Lublow, Michael; Steigert, Alexander; Bogdanoff, Peter; Greiner, Dieter; Kaufmann, Christian A.; Krüger, Martin; Gernert, Ullrich; van de Krol, Roel; Fischer, Anna; Schedel‐Niedrig, Thomas
<x xml:space="preserve">Abstract</x> Novel thin film composite photocathodes based on device‐grade Cu(In, Ga)Se2 chalcopyrite thin film absorbers and transparent conductive oxide Pt‐implemented TiO2 layers on top are presented for an efficient and stable solar‐driven hydrogen evolution. Thin films of phase‐pure anatase TiO2 are implemented with varying Pt‐concentrations in order to optimize simultaneously i) conductivity of the films, ii) electrocatalytic activity, and iii) light‐guidance toward the chalcopyrite. Thereby, high incident‐photon‐to‐current‐efficiencies of more than 80% can be achieved over the full visible light range. In acidic electrolyte (pH 0.3), the most efficient Pt‐implemented TiO2–Cu(In, Ga)Se2 composite electrodes reveal i) photocurrent densities up to 38 mA cm−2 in the saturation region (−0.4 V RHE, reversible hydrogen electrode), ii) 15 mA cm−2 at the thermodynamic potential for H2‐evolution (0 V RHE), and iii) an anodic onset potential shift for the hydrogen evolution (+0.23 V RHE). It is shown that the gradual increase of the Pt‐concentration within the TiO2 layers passes through an efficiency‐ and stability‐maximum of the device (5 vol% of Pt precursor solution). At this maximum, optimized light‐incoupling into the device‐grade chalcopyrite light‐absorber as well as electron conductance properties within the surface layer are achieved while no degradation are observed over more than 24 h of operation.